Sub Maximal Ergospirometry Parameters in Untrained Non-Frail Octogenarian Subjects - Cofre-Bolados, C; De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Background and Objectives: The prevalence of chronic diseases increases with age, and in octogenarian elderly, a cardiorespiratory test with gas analysis is more effective in determining the risk of mortality than applying the conventional risk factors. Materials and Methods: 25 untrained non-frail octogenarian subjects (four men) performed a submaximal test with gas analysis, which was stopped after the second ventilatory threshold (VT2) was reached. The variables analyzed were oxygen consumption at the first threshold (VO2 VT1); ventilatory class (VE/VCO2); oxygen uptake efficiency slope (OUES); cardiorespiratory optimal point (COP); oxygen pulse difference between VT2 and VT1 (diff. VO2/HR VT2-VT1). Results: the variables were classified categorically based on cut-off points present in the literature, where the variable with the highest percentage of altered cases was dif. VO2/HR VT2-VT1 at 48%; followed by VO2 VT1 at 40%, OUES at 36%, COP at 32%, and VE/VCO2 at 24%. Chi-square analysis between the measured parameters defined that normal and altered variables were related to each other, except for the variable VE/VCO2 and OUES. Conclusions: it was found that the main altered variable was the oxygen pulse and the least altered variable was VCO2/VCO2; there was only a statistically significant difference in a pair of OUES vs. VE/VCO2 variables. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.